Role of bone marrow-derived mesenchymal stem cells on the parotid glands of streptozotocin induced diabetes rats - Mona Denewar; Laila E. Amin (Elsevier, 2020)
Background: The functional insufficiency of salivary glands constitute the common oral complaints in both type 1 and type 2 diabetes mellitus. The treatment with stem cell could decrease diabetic-induced hyposalivation and improve the quality of life for patients. Objective: The current study designed to assess the biological outcome of systemic injection of stem cells on the parotid salivary gland in streptozotocin induced diabetic. Methods: Twenty-four albino rats received intra-peritoneal injection of 50 mg/kg streptozotocin for induction of diabetes and were divided into two groups (n = 12): Group I (control) were kept without any manipulation, Group II received intravenous injection of 1×106 of mesenchymal stem cells of bone marrow derived for two days. All rats were sacrificed at 1, 3 weeks, then the parotid glands were isolated, fixed and processed for Heamatoxylin and Eosin examination, immunohistochemical staining for aquaporin-5. Results: group I groups showed intracellular cytoplasmic vacuoles and focal loss of salivary architecture, while group II showed maintenance of gland architecture. Immunohistochemical examination of aquaporin-5 showed significant difference between the two groups. Conclusion: bone marrow derived stem cell treatment considers as an improved methods in prevention and treatment of diabeticinduced hyposalivation.